Proceedings of the 2020 Conference on Empirical Methods in Natural Language Processing (EMNLP) 2020
DOI: 10.18653/v1/2020.emnlp-main.324
|View full text |Cite
|
Sign up to set email alerts
|

Improving Out-of-Scope Detection in Intent Classification by Using Embeddings of the Word Graph Space of the Classes

Abstract: This paper explores how intent classification can be improved by representing the class labels not as a discrete set of symbols but as a space where the word graphs associated to each class are mapped using typical graph embedding techniques. The approach, inspired by a previous algorithm used for an inverse dictionary task, allows the classification algorithm to take in account inter-class similarities provided by the repeated occurrence of some words in the training examples of the different classes. The cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…We present now a formal description of the methodology employed in this work which takes advantage of the intent proto-taxonomies using a neurosymbolic approach. It expands some previous work which focused on the use of keywords as the source of symbolic information (Cavalin et al, 2020). .…”
Section: Using Taxonomic Intent Descriptions To Improve Intent Recognitionmentioning
confidence: 70%
See 2 more Smart Citations
“…We present now a formal description of the methodology employed in this work which takes advantage of the intent proto-taxonomies using a neurosymbolic approach. It expands some previous work which focused on the use of keywords as the source of symbolic information (Cavalin et al, 2020). .…”
Section: Using Taxonomic Intent Descriptions To Improve Intent Recognitionmentioning
confidence: 70%
“…However, the dataset explored in that work is very limited. Recent work has also demonstrated that intent recognition can be improved by enhancing class representations with "keywords" which are extracted from exemplar utterances considering their most common words (Cavalin et al, 2020).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A neural sentence embedding approach representing sentences in a low-dimensional vector space while emphasizing IS characteristics that differentiate from OOS cases was employed in [13]. The OOS classification could also be accomplished by mapping text embeddings of IS data to the groups' word graph space [14]. Furthermore, Kullback-Leibler (KL) divergence is applied in [15] to gather information between the intent distributions of consecutive words.…”
Section: Related Workmentioning
confidence: 99%
“…OOS classification methods are categorized into two approaches, few-shot learning (FSL) and zeroshot learning (ZSL). While FSL tries to create machine learning models using a small amount of OOS training data, such as in this work, Google DialogFlow, and [15], ZSL relies solely on IS training data to detect an OOS like in [13,14]. However, both FSL and ZSL still require labeled IS datasets.…”
Section: Related Workmentioning
confidence: 99%